Cytohesin 2/ARF6 regulates preadipocyte migration through the activation of ERK1/2 - Venkat Kanamarlapudi (Biochemical Pharmacology, 2014)
Preadipocyte migration is vital for the development of adipose tissue, which plays a crucial role in lipid metabolism. ADP-ribosylation factor 6 (ARF6) small GTPase, which regulates membrane trafficking, is activated by GTP-exchange factors (GEFs) such as cytohesin 2. Cytohesin 2 and ARF6 have previously been implicated in the regulation of 3T3-L1 preadipocyte migration. We investigated here the molecular mechanism underlying the cytohesin 2 and ARF6 mediated regulation of preadipocyte migration. Preadipocyte migration and the activation of ARF6 and ERK1/2 were studied by using a number of approaches, including pharmacological inhibitors, siRNA and the inhibitory peptides. The siRNA mediated down regulation of ARF6 and cytohesin 2 expression confirmed the requirement of both for migration of preadipocytes. Phosphatidylinositol 3-kinase (PI3K) and PI 4,5-bisphosphate (PIP2) have also found to be essential for the cytohesin 2/ARF6 induced preadipocyte migration. Pharmacological inhibition of the activation of ARF6, ERK1/2 or dynamin led to significant reduction in migration of 3T3-L1 preadipocytes. Furthermore, our study revealed the activation of ARF6 and ERK1/2 during migration of preadipocytes. In the migrating preadipocytes, ARF6 activation was inhibited with SecinH3 (cytohesin inhibitor) and LY294002 (PI3K inhibitor) whereas the ERK1/2 phosphorylation was inhibited with SecinH3, LY294002, PBP10 (a PIP2 sequester peptide) and PD98059 (MAPKK inhibitor). However, dynosore (dynamin inhibitor) had inhibited neither ARF6 activation nor ERK1/2 phosphorylation during preadipocyte migration. These results together suggest that cytohesin 2 activates ARF6 in a PI3K dependent manner and then the active ARF6 causes phosphorylation of ERK1/2 during preadipocyte migration.